Recycling of plastics with compatibilizer as raw materials for the production of automobile bumper. Issue 1 (1st January 2020) - Adekunle, A.S.; Adeleke, A.A.; Sam Obu, C.V.; Ikubanni, P.P.; Ibitoye, S.E.; Azeez, T.M.
Abstract: Recycled plastic wastes polyethylene terephthalate (PET), high-density polyethylene (HDPE) and polypropylene (PP) were studied in the presence of Ethylene glycidyl methacrylate (EGMA) copolymer compatibilizer, as raw materials for producing automobile bumper. These plastic wastes were cleaned and dried, then crushed to < 3 mm in size and further dried for 4 h to remove moisture. Crushed samples were weighed in different proportions with varying amount of compatibilizer (5–15 g) and manually mixed. Recycled composite plastic of 150 × 150 × 3 mm in length, width and thickness, respectively, was produced from weighed samples in an injection moulding machine at 150–220 o C and pressure of 150 bar. Mechanical tests and morphological observation were carried out on the blend. The mechanical properties were more dependent on EGMA in the blend produced than the variation of the PET, PE and PP. The results showed that the optimum tensile strength (25.48 N/mm 2 ), elongation at break (40.75%), Young's modulus (1615.96 N/mm 2 ) and impact strength (179 J/m) were obtained when 10 g of EGMA was used with 164: 18:18 g of PET, PEL and PP, respectively. The morphology of the sample examined showed the presence of discrete particles with cracks, cavities and various separations, and they defined the mechanical behaviour of the samples. Compared to some standard materials used to produce car bumper, the recycled blend in this study showed huge potential for its production and thus, the use can help in reducing environmental pollution caused by plastic waste.